Tetracycline-like resistome of ancient human guts - Santiago-Rodriguez, Tasha M.; Fornaciari, Gino; Luciani, Stefania; Toranzos, Gary A.; Marota, Isolina; Giuffra, Valentina; Sangwan, Naseer; Cano, Raul J. (Human microbiome journal, 2018)
Tetracyclines were discovered over 70 years ago and their use resulted in the emergence of tetracycline-resistance microorganisms; however, it has been hypothesized that tetracycline-resistance may have originated in the environment, and that determinants were transferred to the human gut microbiota. Ancient microbiomes represent an opportunity to explore the transmission of tetracycline-resistance determinants from the environment to humans. In the present study, tetracycline-like resistomes of three pre-Inca/Inca (10–15th centuries), and five Italian nobility (15–16th centuries) mummies were characterized using high-throughput sequencing. Sequences exhibited low homology to present-day determinants. Results may aid in the understanding of the evolution of tetracycline-resistance.